Effect of Thyromimetic GC-1 Selective Signaling on Reproductive and Lactational Performance in the Hypothyroid Rat. Issue 5 (27th July 2021) - Rinaldini, Estefanía; Verde Arboccó, Fiorella Campo; Ezquer, Marcelo; Gamarra-Luques, Carlos; Hapon, María Belén
Abstract : Introduction: The potential of the thyroid hormone receptor β (TRβ1) selective analog GC-1 has been widely proven in animal models and humans. However, its effect on the reproductive stage of the female rat has not been evaluated. Methods: The effect of the administration of GC-1 or equimolar doses of triiodothyronine (T3) was evaluated on the reproductive performance of the hypothyroid female rat and the indirect effect on pup thyroid status, weight, and survival. Results: Hypothyroidism reduced the number of embryos implanted in the uterus, whereas T3 and GC-1 treatment in hypothyroid females reestablished the number of implanted embryos to normal. Initiation of labor was delayed by hypothyroidism, and T3 replacement treatment reinstated the normal timing of parturition. The administration of GC-1 alone to the lactating mother did not affect pup survival, weight, or thyroidal status. Conclusions: Our findings show the differential effect of thyroid hormone selective signaling during gestation and the indirect exposure of the pups; we also emphasize the plausible use of GC-1 for treatment of hypothyroid mothers during the lactation period.